2021
DOI: 10.4103/jisp.jisp_152_20
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of collagen fibers in human gingival tissues using picrosirius red stain under polarized microscope

Abstract: Background: Collagen fibers are the main element of gingival connective tissue and contribute a leading role in the preservation of structural integrity and tissue function. Hence, its degradation is regarded as the main marker of periodontal disease progression. Aim: The aim of this study is to analyze and compare collagen fibers, their birefringence pattern in healthy and in diseased gingival tissues stained using picrosirius red stain (PRS) and the polarizing microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Specimens were fixed with 4% paraformaldehyde, trimmed, dehydrated, embedded, sliced, dyed, and sealed. The sections were observed under polarized light to evaluate the type, and polarization color of collagen fiber bundles ( 12 ) by an Eclipse CI-L microscope (Nikon, Japan), the birefringent collagens were clearly showed up. With a black background, the stained collagen fibers are represented as bright green to red ( Figures 1D–F ) ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…Specimens were fixed with 4% paraformaldehyde, trimmed, dehydrated, embedded, sliced, dyed, and sealed. The sections were observed under polarized light to evaluate the type, and polarization color of collagen fiber bundles ( 12 ) by an Eclipse CI-L microscope (Nikon, Japan), the birefringent collagens were clearly showed up. With a black background, the stained collagen fibers are represented as bright green to red ( Figures 1D–F ) ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…As expected, when aPDT and UBI29-41 were combined, the ICG@Uio-66-UBI + NIR group exhibited a substantial decrease in collagen degradation. Type I collagen serves as the predominant collagen ber within periodontal ligaments, and its degradation is widely recognized as a primary indicator of the progression of periodontal disease [53,54]. When PAMPs induce an in ammatory response in periodontal tissues, in ammatory cells, broblasts, and epithelial cells upregulate the expression of matrix metalloproteinases (MMPs), leading to a substantial reduction in the amount of type I collagen bers [55].…”
Section: Antibacterial E Cacy Of Different Nps With Respect To Bio Lm...mentioning
confidence: 99%
“…For example, matrix metalloproteinases, namely MMP-8 and MMP-9, are significantly elevated in the GCF of periodontitis patients. [35][36][37] They are markers of collagen degradation, a classic symptom of periodontal disease. 35 However, it has been shown that it is the active form of MMP-8 (aMMP-8) that is a relevant biomarker for periodontitis and periimplantitis rather than the total or latent proMMP-8.…”
Section: Clinical Care Requirements For Poc Devicesmentioning
confidence: 99%
“…[35][36][37] They are markers of collagen degradation, a classic symptom of periodontal disease. 35 However, it has been shown that it is the active form of MMP-8 (aMMP-8) that is a relevant biomarker for periodontitis and periimplantitis rather than the total or latent proMMP-8. 37 The active form of MMP-9, or aMMP-9, is also a useful biomarker for the identification of periodontitis in addition to the latent MMP-9 (IMMP-9).…”
Section: Clinical Care Requirements For Poc Devicesmentioning
confidence: 99%